Tunable Ultraviolet Pulse Generation from a High-Power Self-Similar-Amplification Yb-Fiber Laser - Zefeng Wang; Daping Luo; Gehui Xie; Zejiang Deng; Chenglin Gu; Wenxue Li (Photonics)
A tunable high-power 60 MHz ultraviolet pulse laser directly produced by the extra-cavity fourth-order harmonic generation of a self-similar amplification infrared pulse laser is reported in this study. Utilizing the self-similar pulse evolution and the self-phase modulation in a self-similar amplifier, the system generates a 58.9 W pulse train with a spectral half-width of 85.4 nm, corresponding to a pulse duration of 36 fs. To obtain the ultraviolet pulses from the infrared pulses, a single-pass frequency quadrupling system comprising two cascaded β-BBOs was used. The ultraviolet spectra can be tuned within a spectral range of 253.6 to 275 nm owing to the broadband infrared seed spectra. The maximum ultraviolet average power of 1.44 W was achieved at 275 nm with spectral half-width and an infrared-to-ultraviolet efficiency of 1.1 nm and 2.44%, respectively. To the best of our knowledge, this is the first demonstration of tunable high-power ultraviolet pulse generation from a self-similar amplification Yb-fiber laser.